A histeria no discurso capitalista: a insatisfação do desejo e a falta-a-gozar - Silveira, Renata Rampim (2017)
This work deals with studying hysteria – a basic concept of psychoanalytic theory and praxis – in the capitalist discourse. Instigated by the desire to know about how hysteria presents itself in this discourse, we conducted, at a first moment of the work, a passage on its history, from the Antiquity to Freud, when hysteria and hysterical patients gained a new place. This place is the listening that the father of psychoanalysis destined to the desire of the hysterics. Lacan, in his re-reading of Freud, postulated that hysteria is a strategy regarding the desire, because in its particularity hysteria is defined by the desire of desire. In this way, it constitutes a form of social bond, in the later formulation of Lacan’s theory of discourses. Therefore, if hysteria has its characteristic dissatisfaction of desire, our attention is placed on how this particularity occurs in the capitalist discourse. In this discourse, what prevails is the erasure of the subject and the promise of completeness through objects taken as merchandise, which, in turn, generates a lack-to-enjoyment (manque-à-jouir) in the hysterical subject. However, Lacan postulates that desire is not so easily concealed and, in this sense, hysteria can serve as a resistance against the massification of capitalist discourse, for the dissatisfaction of desire always insists. Finally, we verify which are some possible answers and possibilities of the hysteric before the social bond established by the capitalist discourse, its links and outcomes